Soil legacy effects of plants and drought on aboveground insects in native and range‐expanding plant communities. (22nd November 2022) - Li, Keli; Veen, G. F. (Ciska); ten Hooven, Freddy C.; Harvey, Jeffrey A.; van der Putten, Wim H.
Abstract: Soils contain biotic and abiotic legacies of previous conditions that may influence plant community biomass and associated aboveground biodiversity. However, little is known about the relative strengths and interactions of the various belowground legacies on aboveground plant–insect interactions. We used an outdoor mesocosm experiment to investigate the belowground legacy effects of range‐expanding versus native plants, extreme drought and their interactions on plants, aphids and pollinators. We show that plant biomass was influenced more strongly by the previous plant community than by the previous summer drought. Plant communities consisted of four congeneric pairs of natives and range expanders, and their responses were not unanimous. Legacy effects affected the abundance of aphids more strongly than pollinators. We conclude that legacies can be contained as soil 'memories' that influence aboveground plant community interactions in the next growing season. These soil‐borne 'memories' can be altered by climate warming‐induced plant range shifts and extreme drought. Abstract : Soils contain biotic and abiotic legacies of previous conditions that may influence plant biomass production and associated aboveground biodiversity. We used an outdoor mesocosm experiment to investigate the soil legacy effects of plants, extreme drought, and their interactions on plant biomass production, and on the abundance of aphids and pollinators. We suggest that climate change induces responses of plant range shifts and drought that can be 'memorized' by soil. These memories influence both plant performance and that of aboveground insects in the next growing season.